DAMPAK PENCEMARAN UDARA OLEH PABRIK KELAPA SAWIT DI LINGKUNGAN MASYARAKAT (Studi Kasus Desa Sungai Bawang Kabupaten Kuantan Singingi) - Prastika Sari, Vinni; M Zulherawan (SISI LAIN REALITA, 2022)
The problem of air pollution at this time has reached an alarming level. This is with the increasing  number of pollutant  substances produced from daily activities, the number of factories  and  motorized  vehicles that produce pollutants pollute clean air every day. This is a source of problems for the survival of livinf things. This study aims to describe the public’s response to the impact of air pollution that they feel. Using a qualitative method with a Green Criminology perspective, it was found that the community felt very disturbed by the presence of oil palm companies around their settlements. The community has submitted their complaints to the company, the environmental service, and the people’s representative council. However until this research was carried out, progress had not been made as expected by the community. Even though ghere has been a reaction from the residents on the operation of the palm oil mills around them, there has been no concrete steps from the relevant parties (companies or the government), so that the community is still disturbed to this day.